2008
DOI: 10.1021/la801259n
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Hydroxylation on 3-Aminopropyltriethoxysilane Growth Mode during Chemical Functionalization of GaN Surfaces: An Angle-Resolved X-ray Photoelectron Spectroscopy Study

Abstract: A comparative study of the chemical functionalization of undoped, n- and p-type GaN layers grown on sapphire substrates by metal-organic chemical vapor deposition was carried out. Both types of samples were chemically functionalized with 3-aminopropyltriethoxysilane (APTES) using a well-established silane-based approach for functionalizing hydroxylated surfaces. The untreated surfaces as well as those modified by hydroxylation and APTES deposition were analyzed using angle-resolved X-ray photoelectron spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 27 publications
3
53
0
Order By: Relevance
“…After APTES grafting on the surface, two clear N 1s peaks are detected, which can be assigned to the different attachment modes of APTES (desired silane coupling or non-desired reverse (amino) coupling). Several sources [16,39,40] report that hydroxyl groups on the TiO 2 surface can either react with the Si end of APTES to form a silanized surface or with the amine groups. If silane coupling occurs, the free NH 2 termination is observed at 399.4 eV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After APTES grafting on the surface, two clear N 1s peaks are detected, which can be assigned to the different attachment modes of APTES (desired silane coupling or non-desired reverse (amino) coupling). Several sources [16,39,40] report that hydroxyl groups on the TiO 2 surface can either react with the Si end of APTES to form a silanized surface or with the amine groups. If silane coupling occurs, the free NH 2 termination is observed at 399.4 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Among different functional groups used on TiO 2 for anchoring (phosphonates, carboxylates, silanes), especially silane coupling, is frequently used to attach molecules with a second terminal functionality -often amine -for further modification. A most typical agent is aminopropyl(triethoxy)silane (APTES) that can be used on titania but also on other oxide semiconductors [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. APTES has for example been used as a coupling agent [17][18][19][20], to link proteins [21][22][23] or to promote cell adhesion [24] on TiO 2 surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the contribution of the peak at 399.18 eV is 60.42 % and much higher than that of the peaks at 400.61 eV (24.92 eV) and 401.61 (14.67 eV), APTES appears to be mainly attached by silanized bonding with free terminal NH2 projecting away from the nanoparticle surface, which would be similar to similar to previously reported behaviour. (Pasternack, Amy, & Chabal, 2008;Arranz, Palacio, Garcia-Fresnadillo, Orellana, Navarro, & Munoz, 2008;25 Vandenberg, Bertilsson, Liedberg, Uvdal, Erlandsson, Elwing, & Lundstrom, 1991) The active surface area of the APTES-modified P25 TiO2 nanoparticles as determined using absorption experiments and BET analysis is 47.5 m 2 /g, which is marginally lower (2.5 m 2 /g) than that of the untreated P25 TiO2 nanoparticles (50.0 m 2 /g), due to the coating of APTES on the surface of P25 TiO2 nanoparticle powder. The photocatalytic activity of the P25 TiO2 and APTES modified TiO2 powder was tested by adding samples of the untreated and 5 treated P25 TiO2 nanoparticles to a Rhodamine solution followed by UV-irradiation at 365 nm for 30 min.…”
Section: Modification Of P25 Tio 2 Nanoparticles With Aptesmentioning
confidence: 99%
“…The N 1s peak can be de-convoluted into two, NH 3 + (401.5 eV) and NH 2 (399.8 eV), peaks. 11,12 The NH 3 + peak may also represent a hydrogen bonded NH 2 group (NH 2 ---H). 11,12 The terminal amino group on the NW surface may exist in protonated or de-protonated forms (see Figure 2) at the pH utilized in this study and was also observed by XPS in our previous work utilizing the same pH (pH= 7.4).…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%